The Implications of Mandatory Corporate Social Responsibility—A Literature Review Perspective - Ramdhony, Dinesh (Scientific Research, 2018)
The purpose of this paper is to discuss the implications of mandatory corporate social responsibility (CSR) contributions: the CSR levy. Using public interest theory as the theoretical lens, this paper adopts a pro-regulation approach and justifies the introduction of the CSR levy in Mauritius, based on the economic and business environment prevailing at the time. Secondary literature sources are used to investigate. Two further questions related to mandatory CSR are investigated: Does the CSR levy result in a competitive disadvantage? Does the CSR levy reduce profits? We conclude that the CSR levy does not disadvantage firms due to the uniform amount and its universal application. Furthermore, it can attract Foreign Direct Investment (FDI) and Socially Responsible Investment (SRI). However, the CSR levy does negatively impact on profits but has the potential to pay higher returns in the future if viewed as an investment. This research needs to be complemented by studies that empirically investigate the impacts of the CSR levy on companies and sectors in Mauritius.
Keywords: Mauritius; Mandatory; CSR Levy; Public Interest Theory